Synthesis, Photophysical and Photobiological Study of Synergic Photosensitizer:Zinc-Phthalocyanine with Ca2+ Chelating Agent - Lunardi, Claure N.; G. Rotta, Jeane C.; Tedesco, Antonio C. (Current Organic Chemistry, 2007)
A novel phthalocyanine derivative containing a Ca2+ chelating agent with structure similar to EDTA has been synthesized in 3 steps. The addition of a chelating agent to the phthalocyanine macrocycle make it a synergic compound useful for PDT.
Keywords: fluorescence emission